STUDI KOMPARATIF SARANA KEBERSIHAN LINGKUNGAN DESA MARUS JAYA DENGAN GUGUK DI KECAMATAN RENAH PEMBARAP KABUPATEN MERANGIN - Ratna, Desi - (STKIP PGRI Sumbar, 2014)
Environmental is a area where human and living thing do any activities all at once operate to process ofgrowt and outgrowt. to that life environmental need to kept itâs everlasting and has used as is proper where aliving thing grow to important comprise elements as water, soil and air, own environmental have meaningimportant in every living thing life. the purpose of research to get data, to process data, to analize data and todiscuss about comparative Marus Jaya Village and Guguk Village. The kind of research is ComparativeDescriptive research. The population is 106 Kk whith Marus Jaya Village and Guguk Village. The Teachniqueof data collection use proporsional random sampling with sample sum, 53 patriach respondent Marus JayaVillage and 53 patriarch respondent Guguk Village. Data collection use questionnaire.The result of research is :1) There are difference of water clean supplying where comparison Guguk Village have a lot of use water cleancolour better than Marus Jaya Village. 2) There are difference of rubbish bunishment area supplying wherecomparison Guguk Village have a lot of use rubbish banishmint is burnt better than Marus Jaya Village. 3)There are difference of waste banishment area supplying where comparison Guguk Village have a lot of usesetic tank making is very hecessary better than Marus Jaya Village. 4) There are difference of water closetsupplying where comparison Marus Jaya Village have a lot of use to clean water closet if necessary and hasdirty have a lot of Guguk Village.